Estudio sobre la discriminación de género en cargos gerenciales y juntas directivas de instituciones en la ciudad de Guaranda en el año 2021. - Romero Rodas, Iveth Aracely (2023)
Ecuador is a country in which all the rights that are typified in the Magna Carta, which is the mother of all the legal system, are respected. From this point it is necessary to establish that among these rights is established the right to work, which is also considered as a social duty and economic right, because both women and men maintain the economy of their home based on their working life. The right to work is very important in the life of every human being, since it is a transversal axis in the economic life of every person and their families, it is a duty of the State to guarantee without any type of discrimination the fulfillment of this right. The constitutional right to work, gender equality and non-discrimination are fundamental for each person to have a dignified life in society, since this is the starting point for the respect and evolution that human beings have had over the years and the constant struggle in which workers have been immersed, both men and women have fought for their rights to be fulfilled, Many have given their lives for this cause, although we are currently an apparently developed society that respects the rights, but nevertheless the taboo towards the work done by women is still present, since for society in general there are still jobs that are intended exclusively for men and not for women, even though they have the same capabilities and are in the same conditions. The research project will analyze the possible violation of the right to work, gender equality and discrimination of women in management positions and boards of directors of institutions in Guaranda, Bolivar province and how it affects the emotional and economic stability of women in society. With the result of the present investigation, we seek to help in the solution to the problem found, so that the rights of women are not violated in an unconscious way, but rather that society and the directors of the companies give them the place and position they deserve 5 within the different companies and institutions, so that for the new generations there is no longer any taboo and the rights established in the Magna Carta are respected, both for the benefit of men and women. Keywords: Rights, Economy. Discrimination, Violation, Gender, Equality